AN ANALYSIS OF MAIN CHARACTERS, PLOT AND SOCIAL PROBLEMS IN HIKAYAT SI MISKIN - Nur Widiananta, Yudha (Program Studi Sastra Indonesia, Fakultas Bahasa dan Seni, Universitas Negeri Jakarta, 2023)
This study entitled “An Analysis of Main Characters and Plot in Hikayat Si Miskin” with the aim of describing the characterization of the main character and plot contained in Hikayat Si Miskin. Hikayat is a form of literary work, especially in Malay which contains stories that tell about the greatness and heroism of a person complete with the strangeness, magic and miracles of the main character. The writerss chose the script of Hikayat Si Miskin which has been transcribed by Pusat Pembinaan dan Pengembangan Bahasa in the form of a Transcription book as an object of study. The research approach used in this study is a structural approach. The method used in thi study is descriptive qualitative. The results of this study indicate that the the main character has a patient, compassionate character, willing to sacrifice but easily believes in predictions. Meanwhile the plot in Hikayat Si Miskin built by 5 parts, namely exposition, complication, climax, resolution and conclusion. The social problem is social gap between the rich and the poor.